2005
DOI: 10.1097/01.opx.0000171331.36871.2f
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Clinical Trial of Vision Therapy/Orthoptics versus Pencil Pushups for the Treatment of Convergence Insufficiency in Young Adults

Abstract: : In this study, vision therapy/orthoptics was the only treatment that produced clinically significant improvements in the near point of convergence and positive fusional vergence. However, over half of the patients in this group (58%) were still symptomatic at the end of treatment, although their symptoms were significantly reduced. All three groups demonstrated statistically significant changes in symptoms with 42% in office-based vision therapy/orthoptics, 31% in office-based placebo vision therapy/orthopti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
157
5
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 11 publications
6
157
5
6
Order By: Relevance
“…Thus, reduction in the number of symptoms and their intensity should be correlated with improvement in clinical signs [35] and dynamic responses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, reduction in the number of symptoms and their intensity should be correlated with improvement in clinical signs [35] and dynamic responses [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of 3 rigorously designed comparative treatment studies for convergence insufficiency demonstrated that home-based treatments were not as effective as office-based vergence-accommodative therapy, the studies did show 12 weeks of pencil-push-up alone or in conjuction with home-based computerized therapy to be effective approximately 35% to 40% of the time. [9][10][11] Although the methodological limitations of the study by Serna and colleagues 13 prevent any conclusions to be made regarding the effectiveness of home-based computerized treatment, these results, taken together with those from the CITT, support the need for further investigation of home-based treatments with the objective of determining how their effectiveness can be improved when it is not possible to offer office-based vergence accommodative therapy to children with symptomatic convergence insufficency.…”
mentioning
confidence: 85%
“…However, recent randomized clinical trials funded by the National Eye Institute and completed by the Convergence Insufficiency Treatment Trial (CITT) Study Group have shown that 12 weeks of office-based vergence/accommodative therapy with home reinforcement results in a significantly greater improvement in symptoms and clinical signs as compared with placebo therapy and with home-based treatments that use pencil push-up therapy alone or in conjunction with computer vergence/accommodative therapy. [9][10][11] Despite these findings and the conclusion from the recent Cochrane systematic review for convergence insufficiency that "current research suggests that office-based vision therapy/orthoptics is more effective than home-based pencil push-ups or home-based computer vision therapy/orthoptics," 12 some eye-care providers still prescribed home-based treatments as the primary treatment option, presumably because they do not offer office-based vision therapy/orthoptics in their offices or on account of the low cost and ease of use of home-based therapy.…”
mentioning
confidence: 98%
“…[6] 폭주부족군을 대상으로 집중력이 떨어지는 어린이는 정 상 어린이와 비교하여 3배 이상의 집중력 저하 현상을 보 인다고 하였다. [7] 특히 어린이의 학습능력과 태도는 주의 집중력과도 서로 상관관계가 있으며, 주의집중의 부족과 제한은 일차적인 학습능력 저하의 원인이 된다고 하였다. [8] 학습을 위한 정보의 수집은 약 80% 정도가 시각기관을 통 해 받아들여지므로 [9] [11] 16점 이 상일 경우에 폭주근점 파괴점이 10 cm 미만인 경우는 제 외하였다.…”
Section: 으면 다양한 시지각적 스트레스 증상 및 사물이 왜곡되어unclassified